Biogenic Fe and Mn accumulation in the bottom sediments of Lake Baikal. - Granina, L Z; Zakharova, Yu P; Parfenova, V V (PANGAEA, 2011)
Sediments at the bottom of Lake Baikal are mostly oxidized at their surface, and the oxidized sedimentary deposits are enriched in Fe and Mn hydroxides. The thickness of the oxidized zone of the pelagic sediments averages at 5 cm and locally reaches 10-15, occasionally exceeding 20 cm. Both the thickness of the oxidized layer and the degree of its enrichment in iron and manganese hydroxides are controlled by the depth to which oxygen can penetrate into the sedimentary deposits, which is, in turn, closely related to the sedimentation conditions in the lake (which broadly vary). The sedimentation rate far off the shores of Lake Baikal ranges from <0.02 mm/year to 1.5 mm/year, and the content of organic matter buried in the sediments varies from 0.1 to >4%. The variability of the sedimentation process makes Lake Baikal very convenient to study its diagenetic processes related to redox reactions in sediments, first of all, processes responsible for the redistribution of Fe and Mn compounds. Although the diagenetic enrichment of Fe and Ni in bottom sediments is known to be of biogenic character, very scarce information is available so far on the microorganisms involved in the redistribution of these elements in sediments in Lake Baikal, which lately led us to explore this issue in detail. Our research was centered on the role played by the microbial community in the diagenetic transformations of Fe and Mn with reference to sedimentation conditions in Lake Baikal.
(Table) Bacterial counts and Fe, Mn and SO4 content in sediments and pore waters of two cores from Lake Baikal
Keywords: Archive of Ocean Data; ARCOD; Atomic absorption spectrometry (AAS); Bacteria, iron oxidizing, abundance in colony forming units; Bacteria, manganese oxidizing, abundance in colony forming units; Baikal_1; Baikal_2; Depth comment; Iron; Lake Baikal, Russia; Lake Baikal/Academician Ridge; Layer thickness; Liquid chromatography; Manganese; Manganese 2+; Oxidation reduction (RedOx) potential; pH; pH meter; Sample amount, subset; Sulfate